Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1540-8175.2006.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Tricuspid Regurgitation by Live Three‐Dimensional Transthoracic Echocardiographic Measurements of Vena Contracta Area

Abstract: We evaluated tricuspid regurgitation (TR) by multiple echocardiographic techniques in 93 consecutive patients who underwent standard two-dimensional (2D) and live three-dimensional (3D) transthoracic echocardiography (TTE). TR vena contracta (VC) area was obtained by 3D TTE by systematic and sequential cropping of the acquired 3D TTE dataset. Assessment of VC area by 3D TTE was compared to 2D TTE measurements of the ratio of TR regurgitant jet area to right atrial area (RJA/RAA), RJA alone, VC width, and calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 15 publications
2
65
0
Order By: Relevance
“…Velayudhan et al [31] reported a good feasibility for obtaining the vena contracta area of the tricuspid regurgitant jet from cropping the 3DE color Doppler data set by imaging planes exactly parallel to the TV orifice. The authors also found a poor correlation between the vena contracta area obtained by 3DE and its width measured by 2DE, supporting the concept that, similar to mitral regurgitation, the vena contracta of the tricuspid regurgitant jet has a complex geometry.…”
Section: Functional Tricuspid Regurgitationmentioning
confidence: 99%
“…Velayudhan et al [31] reported a good feasibility for obtaining the vena contracta area of the tricuspid regurgitant jet from cropping the 3DE color Doppler data set by imaging planes exactly parallel to the TV orifice. The authors also found a poor correlation between the vena contracta area obtained by 3DE and its width measured by 2DE, supporting the concept that, similar to mitral regurgitation, the vena contracta of the tricuspid regurgitant jet has a complex geometry.…”
Section: Functional Tricuspid Regurgitationmentioning
confidence: 99%
“…A recent article by Velayudhan et al 128 demonstrated efficacy in measuring the vena contracta of the tricuspid regurgitant jet using 3D color Doppler data. Figure 14 shows an example of the use of color 3D echocardiography to guide vena contracta measurements.…”
Section: Color Tricuspid Regurgitationmentioning
confidence: 99%
“…This finding is understandable because the trileaflet nature of the TV creates a complex VC geometry that is better assessed in 3 than 2 dimensions. 12,14 Older age appeared to be associated with a greater degree of prolapse and annular dilatation. Tethering, however, was seen more frequently in younger patients and might suggest a different underlying mechanism of valve failure.…”
Section: Assessment Of the Severity Of Trmentioning
confidence: 99%
“…Cropping of the RT3D color data set was performed in the 4-chamber view to measure VC area 14 with CardioView software (TomTec Inc, Munich, Germany). When Ͼ1 VC was present, the areas were summed.…”
Section: Measurements Of Vc Area By 3dmentioning
confidence: 99%